Implementasi kurikulum Merdeka Pada Pelajaran PAI di Yayasan Pendidikan Islam SMP IT Khansa Khalifah Medan - Suriono, Ervina Rahma Safira; Selamat Pohan (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This research aims to examine the implementation of the Independent Learning Curriculum in Islamic Religious Education Learning at Khansa Khalifah IT Middle School. This research uses qualitative research with the type of Field Research (field study). Data collection techniques in this research used observation, interview, documentation techniques, as well as 2 (two) types of data sources, namely primary data and secondary data. In collecting primary data, researchers take data directly from informants through interview techniques. The sources used as research objects are Islamic Religious Education teachers and students of SMP IT Khansa Khalifah. Secondary data was collected through documentation carried out by researchers, as well as existing documents, such as school profiles, learning theories and concepts, and data from documents related to the research topic. The research results show that the implementation of the Independent Learning Curriculum in schools has gone well. This is seen from the learning outcomes of students. However, there are several obstacles faced by Khansa Khalifah teachers in implementing the Merdeka curriculum in Islamic Religious Education Lessons at Khansa Khalifah IT Middle School, namely the lack of media facilities and inadequate facilities/infrastructure.